Perencanaan Pencegahan Kecelakaan Kerja Di Pd Sinar Baruna Abadi - Mauluddin, Yusuf; Taptajani, Dedi Sa'dudin; Hilmayanti (Jurnal Kalibrasi, 2025)
The purpose of this study is to identify the factors that cause workplace accidents and to develop a plan to address them. A lack of occupational health and safety, unsafe behavior, and unsafe and unhealthy working conditions have led to accidents during the production process of birthday candles at PD. Sinar Baruna Abadi. To prevent such incidents from recurring, it is necessary to implement controls through an accident prevention plan using the Job Safety Analysis (JSA) and HIRADC (Hazard Identification, Risk Assessment, and Determining Control) methods.The methodology consists of three stages: hazard identification through interviews and field observations, followed by risk assessment by analyzing the likelihood and severity of each potential hazard. The study identified 24 potential hazards in the birthday candle production process, categorized by high, medium, and low risk levels.Planning and control were carried out for five risks with varying values. A risk value of 8 involved activities such as pouring materials and removing candles from molds, with risks of burns and blistered hands. A risk value of 9 was associated with removing candles and dipping them into hot paraffin, posing risks of hand burns and respiratory issues. The highest risk (value 10) occurred during the candle dipping process in hot paraffin, with exposure to hot chemical substances that could cause severe burns.Control measures were focused on risks with values of 9 and 10, including the installation of turbine ventilators to reduce exposure to fumes and vapors.